Expanding legal pathways for labour immigration: A stocktake of the European Commission's efforts - Claire Kumar (ODI Global, 2024)
The European Union (EU) faces a future of chronic labour shortages and increasing global competition for workers. While increasing labour immigration is essential for the EU to maintain its economic security and competitiveness, this remains a neglected topic, amidst debates that focus on irregular migration, deterrence and return. In the context of growing labour and skills shortages, this report examines immigration policy trends and the European Commission's commitments, labour migration directives and operational tools and investments to promote labour migration. It provides analysis of several relevant funding streams - Asylum, Migration and Integration Fund (AMIF) investment via the Migration Partnership Facility and AMIF Action Grants - and lays out recommendations for the Commission in this area.
Keywords: 320